Preliminary study of selected heavy metal contamination in surface sediment of Merambong shoal seagrass bed - Zulkifli, Syaizwan Zahmir; Aziz, Azizul; Ismail, Ahmad; Azmai, Mohammad Noor Amal (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2014)
Surface area of Merambong Shoal Seagrass Bed (MSSB) is an important area for aquatic organisms as well as human communities for fishing activity. Present study was conducted to evaluate the current status of selected heavy metals contamination in surface sediments collected from the MSSB. Samples of surface sediments were collected from multiple locations along MSSB. The heavy metal concentrations of the present study were compared with previously conducted studies in similar location, as well as other location in Malaysia. Geofractionation of heavy metals were also determined. Based on the obtained mean concentration of each metal, a few indices were used to demonstrate the present level of contamination in the surface sediment of MSSB. The findings of this research are important for monitoring heavy metals pollution and conservation management.